Maternal pre‐pregnancy overweight or obesity and risk of birth defects in offspring: Population‐based cohort study - Weiying Liu; Luzhong Ren; Fang Fang; Ruoqing Chen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Maternal obesity, a health condition increasingly prevalent worldwide, has been suggested to be associated with a higher risk of birth defects in offspring, whereas evidence from population‐based data from China was largely lacking. Additionally, the role of gestational diabetes in the association between maternal obesity and birth defects remains unclear. We aimed to investigate the association of maternal pre‐pregnancy overweight or obesity with any and different types of birth defects in offspring and the interaction between pre‐pregnancy overweight or obesity and gestational diabetes. Material and methods We conducted a population‐based cohort study including 257 107 singletons born between 2015 and 2021 in Longgang District, Shenzhen, China, using data from the Shenzhen Maternal and Child Health Management System. Poisson regression was conducted to estimate the associations of maternal pre‐pregnancy overweight or obesity, as well as the interaction between pre‐pregnancy overweight or obesity and gestational diabetes, with the risk of birth defects. Models were adjusted for maternal age at delivery, educational level, type of household registration, and gravidity. Results Maternal pre‐pregnancy overweight was associated with a higher risk of any birth defect (risk ratio [RR] 1.21, 95% confidence interval [CI] 1.12 to 1.31) as well as of congenital malformations of the circulatory system (RR 1.26, 95% CI 1.12 to 1.41), eye/ear/face/neck (RR 1.42, 95% CI 1.04 to 1.94), and musculoskeletal system (RR 1.21, 95% CI 1.01 to 1.44). Maternal pre‐pregnancy obesity was associated with a higher risk of any birth defect (RR 1.38, 95% CI 1.18 to 1.63) and congenital malformations of the circulatory system (RR 1.61, 95% CI 1.30 to 1.98). Infants born to overweight or obese mothers with gestational diabetes had a higher risk of congenital malformations of the circulatory system than infants born to overweight or obese mothers without gestational diabetes. Conclusions Maternal pre‐pregnancy overweight or obesity was associated with a higher risk of birth defects, particularly congenital malformations of the circulatory system, in offspring. Gestational diabetes interacts additively with pre‐pregnancy overweight or obesity on modifying the risk of congenital malformations of the circulatory system. The importance of improving weight management and assessment of glucose and metabolic functions was emphasized among women planning for pregnancy who are overweight or obese.